Policing Empires : militarization, race, and the imperial boomerang in Britain and the US - Go, Julian (New York: Oxford University Press, 2024)
"Policing Empires examines the militarization of the "civil police" in Britain and the United States. It tracks when, why and how British and US police departments have adopted military tactics, tools and technologies for domestic use. It reveals that police militarization has occurred since the very founding of modern policing in the nineteenth century and that militarization has long been an effect of the imperial boomerang. When militarizing their forces, police officials have drawn upon the tactics, tools and technologies associated with imperialism and colonial conquests. Using the tools of comparative and postcolonial historical sociology, the book further shows that there have been distinct waves of militarization in Britain and the United States since the nineteenth century and that each of these waves have been triggered by the racialization of crime and disorder. Police have typically brought the imperial boomerang home to militarize police in response to perceived racialized threats from minority and immigrant populations. Police militarization results from the imperial state domesticating the methods and tools of its armies abroad to herd, contain and thrash imagined barbarians who have dared flood through the gates of ostensible civilization"
A civil police? -- The coloniality of policing -- The birth of the civil police in London, 1829 -- Cotton colonialism and the new police in the US and England, 1830s-1850s -- The new imperialism at home -- Police "reform" and the colonial boomerang in the US, 1890s-1930s -- "Our problems...are not so difficult": militarization and its limits in Britain, 1850s-1910s -- Informal empire and urban insurgency -- Tactical imperialism in the US, 1950s-1970s -- Cycles of policing & insurgency in Britain, 1960s-1980s.
Keywords: Militarization of police -- United States; Militarization of police -- Great Britain; Police -- History. -- United States; Police -- History. -- Great Britain